2021
DOI: 10.1152/jn.00228.2020
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptor modulation of primary afferent excitability with selective regulation of Aδ-mediated spinal actions

Abstract: Somatosensory input strength can be modulated by primary afferent depolarization (PAD) generated via presynaptic GABAA receptors on afferent terminals. We investigated whether acetylcholine (ACh) also provides modulatory actions on PAD via nicotinic acetylcholine receptors (nAChRs) using in vitro murine spinal cord nerve-attached models. Primary afferent stimulation-evoked dorsal root potentials (DRPs) were used as an indirect measure of PAD while evoked afferent transmission was recorded in the deep dorsal ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…We evaluated the proportion of GAD65+ neurons among these neurons ( Figure 1D,E ): 16.4% ± 3.2% of spinal Td-Tomato-positive neurons were GAD65-GFP+ (69 neurons out of 427, n = 3 mice), suggesting that the cortically evoked DRP may be mediated directly by the activation of a GAD65+ spinal target of the CST. In the spinal dorsal horn, cholinergic neurons are a subpopulation of GABAergic neurons ( Todd, 1991 ; Mesnage et al, 2011 ), and cholinergic terminals are known to be presynaptic to primary afferents ( Ribeiro-da-Silva and Cuello, 1990 ; Pawlowski et al, 2013 ) and have recently been shown to modulate primary afferent inputs ( Hochman et al, 2010 ; Shreckengost et al, 2021 ). By performing a similar experiment in ChAT-EGFP mice, we showed that only 2.2% ± 1.8% of CST targets were ChAT-EGFP positive (1 out of 45 neurons, n = 4 mice), limiting the likelihood of a direct major involvement of a cholinergic mechanism ( Figure 1—figure supplement 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the proportion of GAD65+ neurons among these neurons ( Figure 1D,E ): 16.4% ± 3.2% of spinal Td-Tomato-positive neurons were GAD65-GFP+ (69 neurons out of 427, n = 3 mice), suggesting that the cortically evoked DRP may be mediated directly by the activation of a GAD65+ spinal target of the CST. In the spinal dorsal horn, cholinergic neurons are a subpopulation of GABAergic neurons ( Todd, 1991 ; Mesnage et al, 2011 ), and cholinergic terminals are known to be presynaptic to primary afferents ( Ribeiro-da-Silva and Cuello, 1990 ; Pawlowski et al, 2013 ) and have recently been shown to modulate primary afferent inputs ( Hochman et al, 2010 ; Shreckengost et al, 2021 ). By performing a similar experiment in ChAT-EGFP mice, we showed that only 2.2% ± 1.8% of CST targets were ChAT-EGFP positive (1 out of 45 neurons, n = 4 mice), limiting the likelihood of a direct major involvement of a cholinergic mechanism ( Figure 1—figure supplement 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the spinal cord level, sensory gating can be mediated by presynaptic inhibition of sensory inputs through primary afferent depolarization (PAD), a powerful mechanism controlled both by supraspinal centers and by adjacent primary afferents ( Eccles et al, 1962 ). While multiple mechanisms have been demonstrated ( Shreckengost et al, 2021 ), the most studied cause of PAD is presynaptic GABA-A-mediated depolarization. Primary afferents have indeed a high chloride content and respond to GABA by a depolarization that has been shown to reduce the amplitude of incoming action potentials and thus inhibit synaptic transmission ( Prescott and De Koninck, 2003 ; Doyon et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In TdTomato-flex mice crossed with GAD65::GFP mice, we injected a monosynaptic anterograde transynaptic virus (AAV1-CBA::WGA-Cre) encoding the Cre-recombinase fused to the wheat germ agglutinin (WGA) (Libbrecht et al, 2017) 16.4±3.2% of spinal Td-Tomato positive neurons were GAD65::GFP+ (69 neurons out of 427, n=3 mice), suggesting that the cortically-evoked DRP may be mediated directly by the activation of a GAD65+ spinal target of the CST. In the spinal dorsal horn, cholinergic neurons are a subpopulation of GABAergic neurons (Todd, 1991;Mesnage et al, 2011), and cholinergic terminals are known to be presynaptic to primary afferents (Ribeiro-da-Silva and Cuello, 1990;Pawlowski et al, 2013) and have recently been shown to modulate primary afferent inputs (Hochman et al, 2010;Shreckengost et al, 2021). By performing a similar experiment in ChAT::EGFP mice, we showed that only 2.2±1.8% of CST targets were ChAT::EGFP positive (1 out of 45 neurons, n=4 mice), limiting the likelihood of a direct major involvement of a cholinergic mechanism (Figure 1 -Figure Supplement 3).…”
Section: Spinal Targets Of the Cstmentioning
confidence: 99%
“…In rodents nAChRs are also present on primary afferent terminals in the dorsal horn [139,140], and a nicotinic modulation of somatosensory information has been found both in the periphery [141] and centrally on the primary afferent terminals [142,143]. The level of polarization of the terminals is now known to be continuously modulated and different mechanisms are involved.…”
Section: Nicotinic Modulation Of Spinal Motor Circuitsmentioning
confidence: 99%